Neonatal Listeriosis: The Importance of Placenta Histological Examination-A Case Report - Amarilis Batista Teixeira; Ana Maria Arruda Lana; Joel Alves Lamounier; Orlando Pereira da Silva; Silvana Maria Eloi-Santos (Thieme Medical Publishers, Inc., 2011)
Neonatal listeriosis is not a rare disease, but it is infrequently diagnosed and reported in the literature. Herein we report a case of listeria lethal sepsis, followed by increased cytokines levels in the cord blood, in which diagnosis was made possible by histological examination of the placenta.